2023
DOI: 10.3390/foods12061267
|View full text |Cite
|
Sign up to set email alerts
|

Revelation for the Influence Mechanism of Long-Chain Fatty Acid Ethyl Esters on the Baijiu Quality by Multicomponent Chemometrics Combined with Modern Flavor Sensomics

Abstract: Long-chain fatty acid ethyl ester (LCFAEEs) is colorless and has a weak wax and cream aroma. It can be used as an intermediate for the synthesis of emulsifiers, and stabilizers and be applied in the production of flavor essence. It is also an important trace component in Baijiu and is attributed to making a contribution to the quality of Baijiu, but its distribution in Baijiu has not been clear, and its influence mechanisms on Baijiu quality have not been systematically studied. Therefore, the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In detail, propyl hexanoate was the most important regional marker identified by all methods, and the other potential regional markers were ethyl octanoate, ethyl 2‐methylpropanoate, propyl acetate, ethyl heptanoate, ethyl trans ‐4‐decenoate, 2‐nonanone, heptanoic acid and butyl hexanoate. Among them, four esters ((i) produced by bacteria converting acetic acid into butyric acid or caproic acid through metabolism and then reacting with ethanol; (ii) produced by yeast directly using grain) 38 played an important role in distinguishing baijiu production regions and the fact is that Saccharomyces mainly produced ethanol which served as the precursor for synthesizing the ethyl esters during fermentation 39 . The great differences in microorganisms are mainly related to the geographical environment in various production regions, which fully confirmed their reliability as regional markers.…”
Section: Resultsmentioning
confidence: 99%
“…In detail, propyl hexanoate was the most important regional marker identified by all methods, and the other potential regional markers were ethyl octanoate, ethyl 2‐methylpropanoate, propyl acetate, ethyl heptanoate, ethyl trans ‐4‐decenoate, 2‐nonanone, heptanoic acid and butyl hexanoate. Among them, four esters ((i) produced by bacteria converting acetic acid into butyric acid or caproic acid through metabolism and then reacting with ethanol; (ii) produced by yeast directly using grain) 38 played an important role in distinguishing baijiu production regions and the fact is that Saccharomyces mainly produced ethanol which served as the precursor for synthesizing the ethyl esters during fermentation 39 . The great differences in microorganisms are mainly related to the geographical environment in various production regions, which fully confirmed their reliability as regional markers.…”
Section: Resultsmentioning
confidence: 99%
“…The esters may act as sensory modulators by inhibiting the activation of certain receptors that perceive spiciness, resulting in a milder and less intense spicy sensation. Although the addition of LCFAEEs offers benefits like flavor improvement and reduced spiciness, it is important to acknowledge that it also results in a decrease in the intensity of aroma release in the oral cavity [ 11 , 25 , 27 , 54 , 59 , 60 , 61 ]. This can be attributed to the physical properties of the esters, which may impede the diffusion of aroma compounds and their interaction with receptors in the mouth.…”
Section: Resultsmentioning
confidence: 99%
“…Research findings indicated that the pronounced influence of LCFAEEs on the quality of aged Baijiu was verified by combining the distribution of LCFAEEs and sensory evaluation for different years of Baijiu. However, due to the limited number of experimental samples and the years typically spanning 3–5 years, it was not possible to comprehensively reflect the influence of LCFAEEs on the quality of aged Baijiu [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%